Feature based mobile phone rating using sentiment analysis and machine learning approaches - Kafi, Abdullahil; Alam, Md. Shaikh Ashikul; Hossain, Sayeed Bin; Awal, Siam Bin (2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.